Determinants of Islamic Business Unit Performance in Indonesia: Evidence from 2022–2024 - Dupi, Muhamad (Journal of Islamic Economics (JoIE), 2025)
Introduction: Islamic Business Units (Sharia Business Units/UUS) has a strategic value to enhance the Islamic banking system in Indonesia, but its performance in terms of profitability is still unstable, especially during the post-pandemic time. The sustainability of UUS profitability is also questioned because of operational inefficiencies, increased financing risks, and difficulty in intermediation activities. This problem creates the necessity of the empirical study of the main factors that determine the UUS financial performance within the dynamic economic environment. Research Methods: The research method consists of a quantitative research design where the data used are monthlyean values of Sharia Business Units in Indonesia between the period of January 2022 and December 2024. The Yield Proportion, Non-Performing Financing (NPF), Financing to Deposits Ratio (FDR), and Operating Expenses to Operating Income (BOPO) are studied using multiple linear regression to determine their relationship with Return on Assets (ROA). The validity and reliability of the regression model is carried out by classical assumption tests. Findings: The empirical evidence shows that all the explanatory variables, including NPF, FDR, BOPO, and Yield Proportion, have negative impacts on ROA that are significant both in part and at the same time, which indicates that the inefficiency, financing risk, and not optimum intermediation undermine UUS profitability. Conclusion: The paper has concluded that operational efficiency, enhancement of credit risk management and optimization of functions of intermediaries are the main factors needed to increase the profitability of UUS. The findings lead to the Islamic banking literature and offer managerial and policy elucidations on how this is attained through sustainable performance of Sharia Business Units in Indonesia.